(untitled) (Anwer Khan Modern Medical College Journal, 2020)
Dengue virus is the most important mosquito-borne viral disease in the world. Co-circulation of the four types of dengue viruses and expansion of dengue epidemic give rise to infection enhancement and a big expansion of clinical aspects of the disease. Besides dengue, typhoid fever is an ancient disease, have emerged as major public health problem in developing countries including Bangladesh. Here we report a case of 4 years old boy, who have developed Dengue Hemorrhagic Fever within 2 weeks of contemporaneous infection of Typhoid fever and Primary dengue fever. Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 78-81